2006
DOI: 10.1080/00365520500206517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coeliac disease in Italian patients affected by Addison's disease

Abstract: Although we studied only a small sample, our preliminary results confirmed that Addison's disease is associated with coeliac disease, being present in 5.9% of patients with Addison's disease. Since the symptoms can be similar and treatment of Addison's disease can mask coeliac disease, this association should always be actively investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 28 publications
0
4
1
2
Order By: Relevance
“…Histological result would enable to classify these individuals as 'silent' (with typical mucosal lesions but no symptoms) or 'latent' (with normal appearance of intestinal mucosa) celiac disease. Data from our study confirm higher prevalence of celiac disease in AAD patients; however, the proportion of affected subjects (3.5%) is lower in comparison to other European series (5.9-12.2%) [40][41][42][43]. Only one former report stated lower frequency of celiac disease, among Dutch AAD patients (1.2%), but the diagnostic criteria were not provided [12].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Histological result would enable to classify these individuals as 'silent' (with typical mucosal lesions but no symptoms) or 'latent' (with normal appearance of intestinal mucosa) celiac disease. Data from our study confirm higher prevalence of celiac disease in AAD patients; however, the proportion of affected subjects (3.5%) is lower in comparison to other European series (5.9-12.2%) [40][41][42][43]. Only one former report stated lower frequency of celiac disease, among Dutch AAD patients (1.2%), but the diagnostic criteria were not provided [12].…”
Section: Discussioncontrasting
confidence: 58%
“…Studies in other European cohorts revealed high frequency of celiac disease among AAD patients compared to the general population [39][40][41][42]. Moreover, increasing proportion of celiac disease cases remains asymptomatic for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…Other than type 1 diabetes and thyroid autoimmune diseases, further endocrine conditions, such as Addison’s disease [ 87 ] and primary hyperparathyroidism [ 88 ], together with a substantial number of additional immune-mediated disorders [ 89 ] have been reported in association with CD. These include rheumatic and connective tissue diseases, i.e.…”
Section: Associated Diseasesmentioning
confidence: 99%
“…Adrenal cortex autoantibodies or 21-hydroxylase autoantibodies are present in more than 90% of patients at the onset of the disease [82]. The prevalence of CS in patients with Addison’s disease is 5–12% [8386]. Conversely, in a cohort of 14,366 Swedish CS patients, 0.25% of CS patients had Addison’s disease compared with 0.02% of controls (HR: 11.4; 95% CI: 4.4–29.6).…”
Section: Autoimmune Diseases Associated With Csmentioning
confidence: 99%